Influence of cooling rate on ferroelastic domain structure for epitaxial (100)/(001)-oriented Pb(Zr, Ti)O3 thin films under tensile strain. (23rd July 2021) - Ehara, Yoshitaka; Ichinose, Daichi; Kodera, Masanori; Shiraishi, Takahisa; Shimizu, Takao; Yamada, Tomoaki; Nishida, Ken; Funakubo, Hiroshi
Abstract: Epitaxial (100)/(001)-oriented Pb(Zr x Ti1− x )O3 [PZT] films were grown at 700 °C on (100)KTaO3 single crystal substrates by pulsed metalorganic chemical vapor deposition. We investigated the influence of the cooling condition on the ferroelastic domain structure for PZT films under compressive and tensile strains. Under compressive strain, the c -domain fraction ( V c ) was not strongly influenced by the cooling rate. On the other hand, changing the cooling rate caused a significant change in V c in the PZT films grown under tensile strain. In addition, a post-annealing step at a certain temperature below the Curie temperature promoted the formation of a c -domain in the a 1 / a 2 -domain. These results indicate the need to effectively time the formation of the c -domain in the a 1 / a 2 -domain, which is governed by the growth kinetics. The ferroelastic domain structure under tensile stress is determined by the growth kinetics, while a slow cooling rate leads to a thermodynamically stable domain structure.